2004
DOI: 10.1093/nar/gkh082
|View full text |Cite
|
Sign up to set email alerts
|

ProTherm, version 4.0: thermodynamic database for proteins and mutants

Abstract: Release 4.0 of ProTherm, thermodynamic database for proteins and mutants, contains approximately 14,500 numerical data (approximately 450% of the first version) of several thermodynamic parameters along with experimental methods and conditions, and structural, functional and literature information. The sequence and structural information of proteins is connected with thermodynamic data through links between entries in Protein Data Bank, Protein Information Resource and SWISS-PROT and the data in ProTherm. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
281
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(285 citation statements)
references
References 15 publications
4
281
0
Order By: Relevance
“…Similarly, the ΔG o U at 25°C for ecRBP mutants L62C and A188C, using ΔH m values of 81 AE 2 and 91 AE 4 kcal mol −1 , respectively, is 3.2 AE 0.1 kcal mol −1 and 4.1 AE 0.1 kcal mol −1 , whereas the stability of wild-type reported by chemical denaturation is 5.9 AE 0.4 kcal mol −1 (27). This decrease in stability caused by the introduction of cysteine is typical for mutations in the hydrophobic core of these (26,28) and other (29) proteins.…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, the ΔG o U at 25°C for ecRBP mutants L62C and A188C, using ΔH m values of 81 AE 2 and 91 AE 4 kcal mol −1 , respectively, is 3.2 AE 0.1 kcal mol −1 and 4.1 AE 0.1 kcal mol −1 , whereas the stability of wild-type reported by chemical denaturation is 5.9 AE 0.4 kcal mol −1 (27). This decrease in stability caused by the introduction of cysteine is typical for mutations in the hydrophobic core of these (26,28) and other (29) proteins.…”
Section: Resultsmentioning
confidence: 91%
“…4I). Computational modeling showed a decrease in protein stability with a high reliability index (≥3) in six DLC1 mutants, including these three mutants (SI Appendix, Table S16) (42). In addition, using three kinds of bioinformatics algorithms [SIFT (43), PolyPhen-2 (44), and MutationTaster (45)], we found that seven mutations showed "damaging" functional changes, as indicated in multiple analytic algorithms (SI Appendix, Table S17).…”
Section: Association Of Mutations Of Dlc1 With Sensitivity To a Rockmentioning
confidence: 87%
“…Starting either from the protein structure or from the protein sequence, the predictions were done through IMutant2.0 (Capriotti et al, 2005). Here, a data set used derived from ProTherm (Bava et al, 2004) is the database considered when compared against others for thermodynamic experimental data of free energy changes concerning protein stability caused by mutations in various environment. The output files indicated the predicted free energy change value or sign (∆∆G), which was based on the calculation, the unfolding Gibbs free energy value of the mutated protein minus the unfolding Gibbs free energy value of the native protein (kcal/mol).…”
Section: Datasetsmentioning
confidence: 99%